Environmental Law Enforcement in Indonesia Through Civil Law: Between Justice and Legal Certainty - Nugraheni, Prasasti Dyah; Aime, Andrianantenaina Fanirintsoa (Faculty of Law Universitas Negeri Semarang, 2022)
Enforcement of Environmental Law in Indonesia can be done in various ways. One way that can be done is to conduct a lawsuit in Civil Law to the competent court if the plaintiff suffers material or immaterial losses and suffers losses due to environmental damage around his area. There are various court decisions in the civil field, especially the new environmental scope. The new verdict can affect the growth and development of existing Environmental Law in Indonesia. If the plaintiff is the Ministry of Environment and Forestry who suffers material or immaterial losses, then the concept of proof in the judicial process can be called a strict liability suit. The problem written by the author in this journal is the enforcement of Environmental Law in Indonesia through Civil Law. In this journal, the writer uses the normative and juridical writing method, which is a legal writing which is carried out by analyzing secondary legal materials or library materials to find a solution to a legal problem that arises and uses a problem approach based on the laws or general legal rules regarding Environmental Law enforcement in Indonesia through Civil Law and problem approaches that are based on a conceptual basis. The results of research conducted show that to enforce Environmental Law based on Civil Law in Indonesia, judges not only apply existing legal regulations, but judges must also apply other judicial matters so that existing Environmental Laws in Indonesia can experience progress and rapid development.